A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Du, Linlin; Shi, Wenjuan; Li, Xuejuan; Lan, Ying; Sun, Feng; Fan, Yongjian; Zhou, Tong; Zhou, Yijun (Springer, 2019)
Maize rough dwarf disease (MRDD) is one of the most serious viral diseases of maize in China. The object of this study is to develop a reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for rapid and sensitive detection of MRDD pathogen. Four RT-LAMP primers were designed on the basis of S10. Template RNA from infected leaves were used for RT-LAMP which were carried out under isothermal conditions at 61 °C for 90 min. RT-LAMP products were analyzed by electrophoresis in agarose gels or visual inspection of color change after staining with calcein. Sensitivity of the RT-LAMP assay was 100-fold higher than RT-PCR. This method can distinguish RBSDV from SRBSDV and the vectors carrying RBSDV from Rice stripe virus (RSV). The RT-LAMP assay shows excellent potential for application in the rapid and sensitive detection of MRDD pathogens in field samples or vector